Do Earnings Announcements Affect Employee Spending? Evidence from Transaction Data* - Lourie, Ben; Nekrasov, Alexander; Truong, Phong; Zhu, Chenqi (Journal of Accounting Research, 2026)
ABSTRACT Leveraging micro‐level data on individual employees’ bank and credit card transactions, we examine the impact of earnings announcement (EA) news on employee spending. Utilizing an event study methodology, we find strong evidence that EA news elicits significant reactions in employee spending. These reactions are stronger for employees located in the firm's headquarters state, with longer tenure, possessing investment experience, or earning higher wages, consistent with these employees being more likely to attend to their firm's EAs. The reactions are also stronger for the fourth fiscal quarter than interim quarters, suggesting that year‐end results garner greater employee attention. Furthermore, consistent with media facilitating employee processing of EA news, the reactions are stronger for EAs covered by a larger number of news articles. Finally, in line with the notion that EAs contain information about employees’ future cash flows, we find that EA news predicts changes in employee wages and that employees with higher past wage‐to‐EA news sensitivity exhibit stronger spending reactions. Overall, our findings provide evidence of the role of financial reporting in employees’ spending decisions.